Enhancing Chess Skills through Blindfolded Tactics: An Experimental Study on Cognitive and Performance Gains - Giovanni Marchesich; Laura Tamburini (An Overview of Literature, Language and Education Research Vol. 7, 2024)
Blindfold chess is a game where both the board and pieces are not visible to its players. The objective of the project is to explore the cognitive and performance benefits of solving blindfolded tactics compared to traditional methods and to verify the didactic usefulness of these solving tactics in young and adult people, involving an experimental and a control group in the research. A sample of 27 students (14 -30 years old) has been formed and several training sessions with blindfold tactical exercises have been organized. In three months 12 lessons were organized. Then objective measures (not subjective evaluations) of the benefits of this method have been collected by measuring two performance parameters (solving times of exercises and FIDE elo rating change after training sessions) and comparing them with their results before using this method. We analyzed the performance x blindfolding tactics interaction, in particular the correlations between the performance improvement x training interaction and the experimental cognitive path with the three steps of training interaction, compared to participants in the control group. Significant are differences in the improvement in solving tactics times, that is increasing the response speed. Significant results were also found in Rapid FIDE Elo rating improvement, that is increasing the playing force as a function of FIDE rating under vs over 1900 Elo (p >0,05) with a greater improvement for males. In the control group, the interaction is not significant (p>0,5) both in solving tactic times (with an average reduction of 30 seconds for each move) and in FIDE Elo Rating change after the training sessions. The results of this pilot study encourage us to organize a new experimental design in the future with more significant samples to prepare a detailed “Blindfolded tactics training protocol” adaptable to different playing levels of the subjects.